The influence of hydro-meteorological conditions on the dynamics of spawning migration of salmon and lamprey - Evtyukhova, B.K.; Ryapolova, N.I. (Baltijskij Nauchno-issledovatelskij Institut Rybnogo Khozyajstva; "Zvaigzne", 1967)
Salmon Salmo salar and lamprey Lampetra fluviatilis belong to important food fish in Latvia. For the investigations on the spawning migrations of salmon and lamprey the daily catches of these species in the rivers and their correspondence to the chief hydro-meteorological factors - the oscillation of water level in the lower reaches of the river, phases of the moon, and the hydrological background, were analysed. It was established that the daily catches mainly depended on the water level at the mouth of the river. The catches less depended on the phases of the moon and the hydrological background. In addition to the changes in the water level, the absolute height of water was important. In the case the water in the lower reaches of the river was lower of a critical level, the salmon and lamprey catches were absent. The above regularities could be applied for the composition of short-term forecasts (2-3 days in advance) on salmon and lamprey catches, if the prognoses on the water level in the river for a longer period were available. Published Not Known